Rehabilitation of teeth with root canal treatment. Multidisciplinary approach - Flores Concha, Pompeyo H. (2010)
This clinical case details the teeth reconstruction and root canal retreatment, with recovery of the lost biological space invaded by maladjusted crowns and its subsequent reconstruction with fiberglass preformed poles for the cementation of splinted crowns by the decrease of the crown-root proportion. It is concluded that we must take into account the amount of remaining dental tissue, the periodontal status (biological width), the aesthetic requirements, the root morphology, the location of the tooth in the arch and the occlusal loads received.